Enhancement of Random Laser Properties on Solid Polymer Films by Increasing Scattering Effect - Wan Zakiah Wan Ismail; Kami, WMWA; Dawes, JM (Springer, 2024)
Journal of Russian Laser Research volume 40, pages364–369 (2019)